The Effect of the Toothbrushing and Surface Treatments on the Surface Roughness of Interim Crown Materials Used for Conventional, Subtractive, and Additive Manufacturing Techniques: An in Vitro Study - Beşar İzzetağa; Onur Şahin; Ayşegül Köroğlu; Hatice Nalan Bozoğulları (Selçuk University, 2023)
Background: This study aimed to compare the effect of the surface treatment and toothbrushing abrasion on the surface roughness of interim crown material specimens manufactured using conventional, subtractive, and additive processing techniques. Material and methods: 80 disk-shaped specimens were prepared from 4 different interim crown materials; one auto-polymerized polymethyl methacrylate resin (PMMA);(IM) and one bis-acryl composite resin;(AC) for conventional technique, one computer-aided design/computer-aided manufacturing (CAD-CAM) PMMA block;(TC) for subtractive process, one 3-dimensionally (3D) printed resin;(CB) for additive process. Specimens of each interim crown material were divided into two subgroups according to applied surface treatments; conventional polishing or surface sealant agent coupling (n=10). The surface roughness values of specimens before (Ra0) and after 10,000 cycles of toothbrushing (Ra1) were measured with a profilometer. Data were statistically analyzed. Results: The polished groups of all interim crown materials showed significantly higher Ra0 values compared to the sealant groups before toothbrushing (p˂0.05). While the polished IM groups exhibited the highest Ra0 value (0.44±0.08), the sealed TC groups exhibited the lowest Ra0 value (0.23±0.06). The Ra values of all material groups increased after simulated 1-year toothbrushing. While the polished IM group exhibited the highest Ra1 value (0.45±0.14), the sealed CB group had the lowest Ra1 value (0.31±0.09). Conclusion: It was observed that toothbrushing caused an increase in the surface roughness of all interim materials. The application of a surface sealant agent to these materials is more effective than polishing to reduce surface roughness. Sealed 3D printed resin for additive process exhibited the lowest mean roughness value after toothbrushing. Keywords: Additive Manufactured, Interim Crown Material, Roughness, Subtractive Manufactured, Toothbrushing Abrasion